PENGARUH CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING - Ady Purwanto; Lamria Simamora; Iwan Christian (Balance: Media Informasi Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of intensity capital on tax aggressiveness and to analyze the effect of capital intensity on tax aggressiveness which is moderated by corporate social responsibility (CSR). The research method used in this research is descriptive-quantitative research approach. The unit of analysis in this research is the mining sector companies listed on the Indonesia Stock Exchange (BEI), totaling 49 companies with non-probability sampling techniques and using purposive sampling method. The collected data were analyzed using SPSS 24. The results showed that intensity capital had no effect on corporate social responsibility (CSR) aggressiveness, weakening the relationship between capital intensity and aggressiveness